Progressive melanogenesis of angiomatoid Spitz nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
The natural history of Spitz nevus in the child is little known because its rapid growth and the diagnostic difficulties often lead to its early removal. However, there are some agminated angiomatoid Spitz nevi affecting an entire limb that cannot be completely removed. Following these nevi we can see how the single nodules often flatten and take two different paths: some of them undergo atrophy without pigmentation, whereas others turn into barely palpable pigmented melanocytic nevi, as in the current case. While in adults the suspicion of spitzoid melanoma is strong and the removal is not discussed, in the child melanoma is so exceptional before puberty that a probable Spitz nevus can be monitored clinically (1, 2) and the possible removal can be decided according to other criteria such as esthetics, location and the possibility of removal under local anesthesia.